Efeitos da diversidade funcional de detritos sobre a estrutura de comunidades e o funcionamento de ecossistemas de fitotelmatas - Migliorini, Gustavo Henrique [UNESP] (2014)
Understanding the biodiversity effects on community and ecosystem processes is crucial in the face of growing extinction rates and shifts in natural ecosystems. Diversity can influence the consumption of resources governing ecosystem processes through two main mechanisms: (i) complementary properties of species, including niche partitioning and facilitation and (ii) strong dominant species effects on the function of interest (selection effect). Detritus of organic matter (e.g. dead leaves) are the base of primary production in many ecosystems. Detritus functional traits may alter the environment and influence the composition and structure of the associated community, as well as ecosystem functioning. Thus, we investigated if detritus diversity affects the 20 colonization and survival of detritivorous aquatic insects and the detritus processing in phytotelmata of tank bromeliads (Quesnelia arvensis). We manipulated the leaf litter diversity in bromeliads and evaluated the effects on the aquatic invertebrate community (colonization and survival) and a key ecosystem process, decomposition. The higher values of Chironomidae survival were detected for the polyculture (mixed leaf species) and two monocultures (single leaf species); also, the effect of polyculture is greater than the mean of the monocultures. These results indicate a positive selection effect for Chironomidae. Other detritivores (Scirtidae and Trichoptera) were not affected by detritus diversity. Contrary to prediction, decomposition rate was not affected by leaf detritus diversity. This can be explained by the fact that two of three detritivores were not affected in the survival. These two (Scirtidae and Trichoptera) must have, by complementarity, occupied the Chironomidae niche for the detritus consumption. The composition of aquatic and terrestrial colonizing arthropods was affected by detritus diversity. These results indicate that the availability of different resources ...